Antibody response to suckling mouse brain rabies vaccines for post exposure treatment. - Chanthavanich, P; Suntharasamai, P; Warrell, M; Viravan, C; Looareesuwan, S; Supanaranond, W; Karbwang, J; Warrell, D; Phillips, R; Sinhaseni, A (1987)
A new suckling mouse brain vaccine (SMBV) against rabies, produced by the Thai Red Cross Society, was compared with the well established Institut Pasteur SMBV in patients with very low risk rabies contact. The 4 regimens used were the standard daily injections with booster doses of Thai Red Cross vaccine (TRCV) and Institut Pasteur Vaccine (IPV), and a reduced dose scheme of 6 injections as used for tissue culture vaccines. The effect of 20 IU/kg of human rabies immune globulin (HRIG) was tested on each regimen, making 8 groups, a total of 122 patients. Blood samples taken on days 0, 7, 14, 28 and 91 were tested for neutralizing antibody. Only the standard IPV regimen produced antibody in every patient; all had levels greater than 0.5 IU at some stage. Two people (13%) given the standard TRCV produced no detectable antibody (less than or equal to 0.1 IU) throughout the study. The reduced dose regimens gave very low antibody levels. 7% of the IPV and 76% of the TRCV groups failed to produce antibody on any occasion. The antibody response was significantly suppressed by the administration of HRIG. Compared to the original South American SMBV, the vaccines tested induced low levels of short lived antibody. No reduction in the dosage of SMBV should be considered unless the potency of the product is adequate.